Economic Growth and Higher Education Policies in Brazil - Schwartzman, Simon (International Higher Education, 2012)
The relationship between economic growth and higher education in Brazil is discussed in this article. Although Brazil's higher education system is relatively new, it has developed rapidly. In general, however, it has not contributed directly to economic development yet despite some important counter examples.